SARS-CoV-2 Infection Causes Relapse of Kleine-Levin Syndrome: Case Report and Review of Literature - Marino Marčić; Ljiljana Marčić; Barbara Marčić (MDPI AG, 2021)
Recurrent episodes of hypersomnia, hypersexuality, compulsive eating, behavioral and cognitive disturbances, are the basic clinical features of Kleine-Levin syndrome (KLS). Our case report describes a patient who was diagnosed with KLS at the age of 20. With appropriate therapy, the disease had a satisfactory course until patient had a moderate form of SARS-CoV-2 infection, which led to a significant exacerbation of all symptoms. SARS-CoV-2 virus can cause almost any neurological disease, and relapse of KLS is another evidence of neurotropicity of the virus.